Tax avoidance and firm value: evidence from the UK listed company - Wang, Zijue (2018)
Purpose: Testing the relationship between tax avoidance and firm value in the UK is the main Purpose of this research. The second purpose of my research is to test the relationship between tax avoidance and agency costs. Design/methodology/approach: Using a large sample of the UK listed company data from 2008 to 2016 and two regression models. Used Tobin’s q to measure firm value. Tax avoidance was assessed by three measurements. Two of these are based on book-tax difference theory, and the other is based on effective tax rate theory. Agency cost was measured by two different ratios. Findings: Tax avoidance is significantly and positively related to firm value, when tax avoidance is measured by book tax difference (BTD) and TS. Conversely, tax avoidance is significantly and negatively related to firm value when tax avoidance is measured by effective tax rate difference (ETR_D). The results of hypothesis 2 are also at variance. Tax avoidance is significantly and positively related to agency costs when tax avoidance is measured by book tax difference (BTD) and TS. However, when tax avoidance is measured by effective tax rate difference (ETR_D), tax avoidance is significantly and negatively related to agency costs. Originality/value: This paper has contributed to scholarship on corporate tax avoidance in the UK. Before my research, no previous researcher had conducted similar research in the UK. Thus, this is the first evidence to document the relationship between tax avoidance and listed companies’ value in the UK.